2013
DOI: 10.1186/1471-2458-13-1233
|View full text |Cite
|
Sign up to set email alerts
|

Influence of stressors and possible pathways of onset of seventh graders’ suicidal ideation in urban and rural areas in Taiwan

Abstract: BackgroundSuicide is the second leading cause of death among young people in Taiwan. However, few studies have investigated children’s suicidal ideation, and longitudinal studies are particularly rare. The purposes of this study were: (1) to describe the proportion of students with suicidal ideation in one month and incidence of suicidal ideation in the 7th graders (the first year of junior high school) living in urban and rural areas; (2) to realize the influence of perceived stressors on the onset of 7th gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…In cases where multiple studies assessed the same SITB prevalence or correlate in overlapping samples, determination of which study to include in the meta-analysis was based on largest sample size for relevant analyses. Twenty-one studies featured overlapping samples, and 7 were excluded at this stage, leaving a final set of 58 studies featuring 52 samples (Figure; eTable 1 in the Supplement).…”
Section: Resultsmentioning
confidence: 99%
“…In cases where multiple studies assessed the same SITB prevalence or correlate in overlapping samples, determination of which study to include in the meta-analysis was based on largest sample size for relevant analyses. Twenty-one studies featured overlapping samples, and 7 were excluded at this stage, leaving a final set of 58 studies featuring 52 samples (Figure; eTable 1 in the Supplement).…”
Section: Resultsmentioning
confidence: 99%
“…In Taiwan, this stress increases dramatically by the seventh grade; students exhibit low self‐competence and poor academic performance (Chiang et al . ). Stress can impair cognitive skills, even in children without a disability.…”
Section: Introductionmentioning
confidence: 97%
“…The pressure to achieve begins at an early age in eastern Asian cultures, and education and high examination scores are important for upward mobility. In Taiwan, this stress increases dramatically by the seventh grade; students exhibit low self-competence and poor academic performance (Chiang et al 2013). Stress can impair cognitive skills, even in children without a disability.…”
Section: Introductionmentioning
confidence: 99%
“…This study also found that Adolescents living in rural areas are at significantly lower risk of suicide than their urban peers. The reason for this may be that urban children face far greater academic pressure than rural children and the pace of life is much faster than in the countryside ( 61 ). In addition, the interpersonal relationship in the countryside is better than in the city, the resulting sense of apathy can also lead to psychological problems, and even affect an individual's behavior and eventually lead to suicide ( 62 ).…”
Section: Discussionmentioning
confidence: 99%